Current economic and diplomatic aspect of Ukrainian-Czech relations - Рєзніков, Валерій; Бороденко, Михайло (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism)
The article studies the Ukrainian-Czech relations from the perspective of economic diplomacy. It reveals condition and prospects of foreign economic activities between the two countries, considers investment and commodity component. The article shows the interdependence of diplomatic and foreign economic aspects of cooperation between the countries.